A New Species of Burmeistera (Campanulaceae, Lobelioideae) from the Pacific Slope of the Northwestern Andes of Colombia - Zapata-Correa, Diego Alejandro; Garzón-Venegas, Javier; Caro Holguín, Andrés Felipe; Ruiz Molina, Daniel (Phytotaxa, 2024)
A new species of Burmeistera (Campanulaceae, Lobelioideae) from the Pacific slope of the Northwestern Andes of Colombia, in the Antioquia and Chocó departments, is described. Burmeistera luciae is distinguished by being a hemiepiphytic herb with scandent and glabrous stems; ebracteate peduncle, obconic hypanthium, and its most particular feature, the filiform, ascending, and curved calyx lobes in anthesis; corolla lobes forming an obtuse angle in relation to the tube, falcate; ventral anthers barbate; ellipsoid berries that turn a striking fuchsia color when mature. These characters differentiate it from Burmeistera serraniaguae, B. succulenta, and B. crocodila, the three most morphologically similar species that also inhabit the humid Andean regions of the Chocó biogeographic region between Colombia and Ecuador. Additional comments related to its distribution, etymology, and conservation status are presented.